Final five‐year results of the REMEDEE Registry: Real‐world experience with the dual‐therapy COMBO stent. Issue 3 (8th October 2020) - Kerkmeijer, Laura S.M.; Chandrasekhar, Jaya; Kalkman, Deborah N.; Woudstra, Pier; Menown, Ian B.A.; Suryapranata, Harry; den Heijer, Peter; Iñiguez, Andrés; van 't Hof, Arnoud W.J.; Erglis, Andrejs; Arkenbout, Karin E.; Muller, Philippe; et al.
Abstract: Objectives: This final report from the REMEDEE Registry assessed the long‐term safety and efficacy of the dual‐therapy COMBO stent in a large unselected patient population. Background: The bio‐engineered COMBO stent (OrbusNeich Medical BV, The Netherlands) is a dual‐therapy pro‐healing stent. Data of long‐term safety and efficacy of the this stent is lacking. Methods: The prospective, multicenter, investigator‐initiated REMEDEE Registry evaluated clinical outcomes after COMBO stent implantation in daily clinical practice. One thousand patients were enrolled between June 2013 and March 2014. Results: Five‐year follow‐up data were obtained in 97.2% of patients. At 5‐years, target lesion failure (TLF) (composite of cardiac death, target‐vessel myocardial infarction, or target lesion revascularization) was present in 145 patients (14.8%). Definite or probable stent thrombosis (ST) occurred in 0.9%, with no additional case beyond 3‐years of follow‐up. In males, 5‐year TLF‐rate was 15.6 versus 12.6% in females ( p = .22). Patients without diabetes mellitus (DM) had TLF‐rate of 11.4%, noninsulin‐treated DM 22.7% ( p = .001) and insulin‐treated DM 41.2% ( p < .001). Patients presenting with non‐ST segment elevation acute coronary syndrome (NSTE‐ACS) had higher incidence of TLF compared to non‐ACS (20.4 vs. 13.3%; p = .008), while incidence with STE‐ACS was comparable to non‐ACS (10.7 vs. 13.3%; p = .43). Conclusion: Percutaneous coronary intervention with the dual‐therapy COMBO stent in unselected patient population shows low rates of TLF and ST to 5 years. Remarkably, no case of ST was noted beyond 3 years.